Randomized Controlled Trial of Telephone-delivered Cognitive Behavioral Therapy Versus Supportive Care for Chronic Back Pain. Issue 4 (April 2018) - Rutledge, Thomas; Atkinson, J. Hampton; Chircop-Rollick, Tatiana; D'Andrea, John; Garfin, Steven; Patel, Shetal; Penzien, Donald B.; Wallace, Mark; Weickgenant, Anne L.; Slater, Mark
Abstract : Objective: The objective of this study was to evaluate the efficacy of a telephone-delivered, home-based cognitive-behavioral intervention for chronic low back pain in comparison to a matched supportive care (SC) treatment. Methods: Participants (N=66) were patients with chronic back pain that were randomized to either an 8-week Cognitive-Behavioral Therapy (CBT) or a SC condition matched for contact frequency, format, and time. Participants completed validated measures of improvement in back pain disability, pain severity, and overall improvement. Results: Intent-to-treat analyses at posttreatment showed that the treatment groups not show significantly different improvements in back pain disability (mean changes, −2.4 and −2.6 for CBT and SC, respectively; Cohen d, 0.49 and 0.55, respectively) or reductions in pain severity (mean changes, −0.9 and −1.4 for CBT and SC respectively; Cohen d, 0.50, and 0.90, respectively). Participants rated their overall improvement levels at 31% (CBT) versus 18.5% (SC). Discussion: Results from this clinical trial suggest that home-based, telephone-delivered CBT and SC treatments did not significantly differ in their benefits for back pain severity and disability, and may warrant further research for applications to hospital settings. Major limitations included recruitment difficulties that underpowered primary analyses, the lack of objective improvement measures, and the absence of a usual care/untreated control group for comparisons.